Efficacy and safety of hydroxyurea therapy on patients with β-thalassemia: a systematic review and meta-analysis - Huang, Tianmin; Jiang, Huixian; Tang, Ganling; Li, Jingyi; Huang, Xiaoman; Huang, Zhenguang; Zhang, Hongliang (Frontiers in Medicine, 2025)
ObjectiveOur aim is to review the safety and efficacy of hydroxyurea (HU) on β-thalassemia patients.MethodsStudies that evaluated the safety and efficacy of HU on β-thalassemia patients were searched in Pub-Med, Cochrane Databases, Web of Science, China-Biology-Medicine, CNKI, Embase, VIP, and WanFang data. The proportions of response rate (RR) (50% fall in transfusion need in transfusion-dependent β-thalassemia patients, or 1 g/dL elevate in hemoglobin (Hb) levels in transfusion-independent β-thalassemia patients) and good RR (transfusion-free in transfusion-dependent β-thalassemia patients or 2 g/dL elevate in Hb levels in transfusion-independent β-thalassemia patients) were utilized to evaluate the effect size (ES). The secondary outcomes were the adverse events incidence rates of HU in β-thalassemia patients.ResultsTwo randomized controlled trials (RCTs) and 25 single-armed observational studies with typically 1,748 individuals were involved in our analysis. All 27 clinical trials were reported with fair quality. HU, in transfusion-dependent β-thalassemia patients, was related to a significant decrease in transfusion requirements [a pooled RR of 0.37 and a pooled good RR of 0.65 (95% CI, 0.53–0.76)]; in transfusion-independent β-thalassemia patients, it was correlated to an excellent raise in Hb levels [a pooled RR of 0.20 (95% CI, 0.08–0.35) and a pooled good RR of 0.53 (95% CI, 0.41–0.65)]. Neutropenia and leucopenia were the most prevalent adverse events in β-thalassemia patients treated with HU, while the incidence rates of other side effects were relatively lower.ConclusionOur findings demonstrated that β-thalassemia patients tolerated and responded well to HU. Due to the control arms absence in the involved studies, more double-masked RCTs are essential for proving the safety and efficacy of HU in β-thalassemia patients.